Comprehensive assessment of left atrial and ventricular remodeling in paroxysmal atrial fibrillation by the cardiovascular magnetic resonance myocardial extracellular volume fraction and feature tracking strain - Yamada, Akimasa; Hashimoto, Naoki; Fujito, Hidesato; Hatta, Takumi; Saito, Yuki; Otsuka, Naoto; Wakamatsu, Yuji; Arai, Masaru; Watanabe, Ryuta; Kurokawa, Sayaka; Kitano, Daisuke; Nagashima, Koichi; et al. (Scientific reports, 2021)
Atrial fibrillation (AF) is a progressive disease that starts with structural or functional changes in the left atrium and left ventricle, and evolves from paroxysmal toward sustained forms. Early detection of structural or functional changes in the left atrium and left ventricle in the paroxysmal stage could be useful for identifying a higher risk of progression to persistent AF and future cardio-cerebrovascular events. The aim of this study was to test the hypothesis that the feature tracking (FT) left atrial (LA) strain and left ventricular (LV) extracellular volume fraction (ECV) derived from cardiovascular magnetic resonance (CMR) could detect early changes in remodeling of the left atrium and ventricle in the paroxysmal AF (PAF) stage. The participants were comprised of 106 PAF patients (age, 66.1 ± 10.7 years; 66% male) who underwent clinical CMR before pulmonary vein isolation and 20 control subjects (age, 68.3 ± 8.6 years; 55% male). The CMR-FT LA strain/phasic function and LV-ECV were compared between the PAF and control groups. The total and passive LA empty fraction (LAEF) and LA strain (corresponding to LA reservoir and conduit function) were decreased in the PAF group as compared to the control group. However, active LAEF (corresponding to the LA booster pump function) did not differ significantly between the PAF group (33.9 ± 10.9%) and control group (37.9 ± 13.3%, p = 0.15), while the active LA strain (corresponding to the LA booster pump function) was significantly decreased in the PAF group (11.4 ± 4.3 vs. 15.2 ± 5.6%, p = 0.002). The LV-ECV was significantly greater in the PAF group (28.7 ± 2.8%) than control group (26.6 ± 2.0%, p = 0.002). In the PAF group, the LV-ECV correlated significantly with the E/e′ and LA volume index. Regarding the LA strain, correlations were seen between the LV-ECV and both the reservoir function and conduit function. CMR-FT LA strain in combination with the LV-ECV in a single clinical study offers a potential imaging marker that identifies LA/LV remodeling including subtle LA booster pump dysfunction undetectable by the conventional booster pump LAEF in the PAF stage.